Aspectos da reprodução e da alimentação de Pseudoplatystoma punctifer (Castelnau,1855) (Siluriformes, Pimelodidae) na bacia do rio Teles Pires, Alta Floresta- MT - Luca, Alexander Stein de (2010)
This study was conducted in the middle portion of the Teles Pires river basin and four tributaries, from october 2007 to july 2009, the Alta Floresta region in northern Mato Grosso. The objective was to study the reproduction and diet of the cachara Pseudoplatystoma punctifer. Sampling of fish were collected monthly by using longlines placed on the banks of rivers, Stopped, Four Bridges, Santa Helena, Apiacás, Teles Pires and in Lagoa da Mata, The specimens captured were killed and underwent biometry were removed gonads and stomach identifying the sex and stage of gonadal maturation the naked eye. We estimated the degree of stomach fullness, frequency of occurrence for each item and feeding. Measurements of abiotic variables were collected at the sites of P. punctifer. We made monthly measurements of water temperature, transparency, conductivity, dissolved oxygen and pH always two stations in each area to collect fish. We collected 398 fish, and of these 223 are females and 175 are male, accounting for 56% and 44%, respectively. There was a differentiation in size and weight of the ovaries with the variation of the reproductive cycle, the ovaries of young immature body weights minimum of 4.5 g, reaching a maximum weight of 630 g in adult females mature testes weight ranged on average from 2.6 g to 474.0 g young immature to mature adults. During the water regime was a variation in the absolute frequency of occurrence of females and males at different stages of gonadal development. The young, males and females predominated in all the phases with higher frequency in the flood of 2008 for both sexes, reproductive adults predominated in the flood of 2009, with most males, males and females in reproductive adults not predominant in all home phases of the hydrological regime in the flood of 2009 for females and males from 2008 to ebb. You can measure the spawning P. punctifer occurs between January and February, with completion in april 2009, coinciding with the highest values of rainfall in the region. For females the estimated L50 was 72.5 cm and for males was 72.0 cm, (L100) is greater in females at 106 cm for males, 94.5 cm. Females were more numerous in the length classes between 63.0 cm to 81.0 cm, males in length classes from 58.0 cm to 78.0 cm. The sex ratio is presented as follows: between the months of october 2007 to march 2008, the ratio was 1 male to female and three months from november to december 2008 was the first male to 17 females. The estimated averages of condition factor (K) depending on the water regime, were higher among males in the full flood of 2008 and 2009, the female values were balanced, the condition presented by individuals during the study period did not vary significantly depending on the water regime. Among abiotic factors analyzed, rainfall indirectly contributing to reproduction of P. punctinfer. The seasonality, characterized by the phases of water regime in the region, influenced the greater supply of items to the diet, especially the full. Despite the great contribution of fish in the diet of P. punctifer, diversity of food items indicates a carnivorous diet generalist, because it presents no selectivity of prey including several families of fish and other food groups. The presence of terrestrial vertebrates in this study may indicate an opportunistic habit of the species.